Toxic epidermal necrolysis-like acute cutaneous lupus erythematosus (Ten-like ACLE) in SLE patients: A report of two cases - Einapak Boontaveeyuwat (2018)
Background: Acute cutaneous lupus erythematosus (ACLE) is a specific lesion in systemic lupus erythematosus (SLE) patients. ACLE can be categorized into localized ACLE, generalized ACLE and toxic epidermal necrolysis-like ACLE. Toxic epidermal necrolysis (TEN) that occurs in SLE patients has been infrequently reviewed. This condition is complicated to diagnose because medication can produce a blistering eruption that resembles vesiculobullous disease in SLE. Objective: To describe two cases of newly diagnosed SLE that had a cutaneous presentation compatible with TEN-like ACLE. Case reports: Characteristics of two patients presenting with TEN-like ACLE and SLE are presented. Conclusion: The authors have described two cases of TEN-like ACLE which occurred in the context of systemic involvement of SLE. The cutaneous lesion was gradually progressed, with less mucosal involvement and mainly photodistributed. The authors suggest that the complexity and rarity of this condition could be related to systemic severity of SLE.